Pengembangan Sistem Pengelolaan Obat Pada Instalasi Farmasi Puskesmas Seroja Bekasi Berbasis Web - Nur Lia Afriza; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Medicines management at a health center has a significant role because it aims to ensure the availability of medicines. The availability of medicines at a health center is affected by the medicines procurement process. The problem of medicines management at Seroja Health Center is the difference in the amount of medicines stock that is recorded in books with the physical data. One of the reasons is caused by human error in the process of recording incoming medicines and outgoing medicines. The wrong recording will make it difficult for the pharmacist to make medicines expenditure report and medicines stock report. The pharmacist will also have difficulty in calculating medicines needs planning. Incorrect planning can make ordering unplanned medicines that have to be fulfilled immediately cause some medicines are over-stock or lack of stock. Medicines management system is developed to overcome these problems. This system is expected to help the process of medicines management at Seroja Health Center, especially in recording, reporting, and simplifying the calculation of medicines needs. The process of developing this system is done using the waterfall model. The stages performed in this research include literature review, requirements, design, implementation, testing, and decision-making. This system uses web technology that allows it to be accessed easily through a web browser. This system has been tested using white box testing for unit testing and integration testing and black box testing for validation testing. The results from all testing give valid status